Penerapan Pembelajaran Kooperatif Tipe Jigsaw III Untuk Meningkatkan Hasil dan Motivasi Belajar Biologi Kelas I7 SMAN 4 Pekanbaru Tahun Ajaran 2003/2004 - Yusuf, Yustini; Suryawati, Evi; Rosnetti, Santi; Awal, Rauda (Jurnal Pilar Sains, 2005)
Have been done by research of action Class to increase result and motivation learn Biology byapplying model study of type co-operative Jigsaw III at class student one SMAN 4 Pekanbaru in apriluntil mei 2004. The research subject is class student 17 with amount 43 people. Parameter themeasured is result learn student, complete learn, activity learn motivation and student learn. Resultlearn cycle of 17 mean 74.23 % mounting, at cycle II mean 80.35 %. Complete learn cycle of I is 76.74% (is not complete), at cycle of II is 93.02 % (is complete), for the activity of student at group comefrom at cycle of I mean 75.12 % and mount to become 85.47 % at cycle of II. Activity expert group55.47% at cycle of I and 64.52% at cycle of II. Motivation learn student biology at cycle student of Inatural is make-up of with percentage mean of is make-up of motivation 35.77% and mean score 2.80.At cycle of II natural is make-up of with percentage mean is make-up of motivation 8.10% and meanscore 3.03. From result of research can be concluded that applying of study of type co-operative ofJigsaw III can improve result, motivation and activity learn class student 17 SMAN 4 Pekanbaru.